2014
DOI: 10.1088/0004-637x/789/2/107
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Flare Dynamics of Sunspot Groups

Abstract: Several papers provide evidences that the most probable sites of flare onset are the regions of high horizontal magnetic field gradients in solar active regions. Besides the localization of flare producing areas the present work intends to reveal the characteristic temporal variations in these regions prior to flares. This study uses sunspot data instead of magnetograms, it follows the behaviour of a suitable defined proxy measure representing the horizontal magnetic field gradient. The source of the data is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
6
21
0
3
Order By: Relevance
“…17 in (Abramov-Maximov et al, 2015)). Note that a similar evolution of the magnetic field gradient before X flares was observed in (Korsos et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…17 in (Abramov-Maximov et al, 2015)). Note that a similar evolution of the magnetic field gradient before X flares was observed in (Korsos et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…fluxes, shear formation, and high magnetic gradients along the neutral line can be precursors of large flares (Falconer et al, 2002;Cui et al, 2006Cui et al, , 2007Wang, 2006;Schrijer, 2007;Steward et al, 2011). Unlike the authors of these studies, who used only magnetograms for the analysis, Korsos et al (2014Korsos et al ( , 2015 analyzed the parameters of sunspot groups in a number of flare regions. They concluded that, before large flares, a sharp increase in the magnetic field gradient was observed, reaching a maximum, which was followed by its decrease immediately before the flare.…”
Section: Introductionmentioning
confidence: 99%
“…The solar flare forecasting model is trained and tested on the Caffe platform (Jia et al 2014), which is a deep learning framework developed by the Berkeley Vision and Learning Center. In the training phase, weights in the forecasting model are iteratively adjusted to minimize the value of the training error on the MDI data.…”
Section: Training On MDI Data and Testing On Hmi Datamentioning
confidence: 99%
“…It is obvious that the morphological classification of sunspots is artificial, and physical parameters are more reasonable measures for the complexity and nonpotentiality of active regions, for example, the length of the neutral line (Falconer 2001), the gradient of the magnetic field (Cui et al 2006), the highly stressed longitudinal magnetic field , the distance between active regions and predicted active longitudes , the Zernike moment of magnetograms (Raboonik et al 2016). Furthermore, The evolutions of physical parameters in active regions were studied in , Huang et al (2010), and Korsós et al (2014Korsós et al ( , 2015. Besides that, Wheatland (2004) suggested that the history of solar flares is an important predictor for subsequent flares.…”
Section: Introductionmentioning
confidence: 99%
“…This catalog contains valuable data on position, area, and mean magnetic field for each sunspot and sunspot group. Korsós et al (2014), henceforth Paper I, investigated the preflare behavior of the horizontal magnetic gradient (G M ) parameter. They found that G M exhibits characteristic pre-flare patterns: a steep rise until a maximum, followed by a gradual decrease for several hours and then the outburst.…”
Section: Classifications Of Morphological Complexitymentioning
confidence: 99%